PENGARUH JENIS KEMASAN DAN TINGKAT KEMATANGAN TERHADAP KUALITAS BUAH JERUK SELAMA PENYIMPANAN - Desy Nofriati; Nur Asni (Balai Besar Penelitian dan Pengembangan Pascapanen Pertanian, 2015)
Packaging and maturity levels are considered to be two most important determinant factor that may affect of freshness the citrus duringstorage. The objective of the study to find out the best type of packaging and maturity levels to weights loss and damage of productduring storage. The experimental used randomized factorial design that the maturity levels as the first factor and type of packagingas the second factor and LSD analysis testing followed if there are significant differences among the treatment. The result indicatesthat type of package and the maturity levels affected of citrus quality during storage. The Packaging with the ventilated cardboard boxand plastic crate are the best packing in protecting for citrus fruit and than prolong it shelf life for 16 days of storage. The over maturityshowed the higher weight loss value than green maturity and the optimum maturity levels.